Evaluation of Quality Improvement Methods for Altering Opioid Prescribing Behavior in Hand Surgery. (6th May 2020) - Schommer, Jillian; Allen, Scott; Scholz, Natalie; Reams, Megan; Bohn, Deborah
Abstract : Background: The opioid epidemic in the United States continues to be problematic as morbidity and mortality rates increase yearly. Orthopaedic surgeons are the third highest prescribing group among physicians. Studies show that orthopaedic surgeons tend to overprescribe opioids, but published data on patient opioid utilization, pain management satisfaction, and national clinical practice guidelines on opioid prescribing are scarce or lacking. Furthermore, little information is available on influences on physician prescribing behavior and whether changes in prescribing habits are lasting. Methods: Using recently published opioid utilization and prescribing guidelines for hand surgery, we created an opioid prescribing quality improvement program with the aim of reducing postoperative opioid prescribing without negatively impacting patient pain satisfaction. The main aspect of the program was the implementation and modification of an opioid prescribing order set, but the program also included surgeon education—executed in 2 intervention steps—about how their prescribing behavior compared with that of their peers. Three phases of data representing 3 months each were collected prior to, between, and after the interventions. Results: Two thousand and sixty-seven hand surgery cases were reviewed (629 in Phase 1, 655 in Phase 2, and 783 in Phase 3). The average number of morphine milligram equivalents (MMEs) was reduced from 142.0 in Phase 1 to 69.9 in Phase 2 (51% reduction) to 61.3 in Phase 3 (57% reduction compared with Phase 1). Significant reductions in MMEs occurred across the procedural categories as well as the hand surgeons. Patient pain satisfaction was similar before and after implementation of the first intervention (p = 0.96). Conclusions: Quality improvement methods were effective in altering prescribing behavior by physicians in the long term, and our approach may be effective if applied more widely. Similar studies on quality improvement methods and prescribing behavior, patient opioid utilization, and patient satisfaction with pain management are needed in other orthopaedic subspecialties. Clinical Relevance: Evidence-based guidelines, a quality improvement process, and unblinded information on prescribing behavior compared with that of peers may result in long-lasting reductions in surgeons' opioid prescribing practices.